Switching device

The switch device addresses glass layer damage by using a composite structure with a glass layer sandwiched between resin layers, achieving durability and consistent operation.

JP2025058524APending Publication Date: 2025-04-09NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023168509
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-04-09

AI Technical Summary

Technical Problem

Switch devices with a composite having a glass layer face damage issues to the glass layer, which needs to be addressed to ensure durability and functionality.

Method used

The switch device incorporates a composite structure with a first resin layer, a glass layer laminated on the lower surface of the first resin layer, and a second resin layer laminated on the lower surface of the glass layer, where the thickness of the glass layer is between 30 μm and 150 μm, and the composite is elastically deformed to switch the switch between conduction and non-conductivity.

Benefits of technology

This configuration effectively suppresses damage to the glass layer, ensuring the switch device's durability and maintaining a consistent click feeling during operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025058524000001_ABST
    Figure 2025058524000001_ABST
Patent Text Reader

Abstract

To suppress damage to a glass layer in a switching device including a composite having a glass layer.SOLUTION: A switching device includes a composite including a first resin layer, a glass layer laminated on the underside of the first resin layer, and a second resin layer laminated on the underside of the glass layer, and a switch arranged on the underside of the second resin layer of the composite, and the thickness of the glass layer is 30 μm or more and 150 μm or less, and when the composite is pressed, the composite is elastically deformed, causing the switch to switch between conductive and non-conductive states.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a switch device. [Background technology]

[0002] A switch device is known that has a composite having a glass layer as an outermost layer and a switch arranged on the underside of the composite, in which when the composite is pressed, the composite elastically deforms, causing the switch to switch between conductive and non-conductive states. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2022-166480 A Summary of the Invention [Problem to be solved by the invention]

[0004] In a switch device including a composite body having a glass layer as described above, it is preferable to take measures against breakage of the glass layer.

[0005] An object of the present invention is to suppress breakage of a glass layer in a switch device including a composite having a glass layer. [Means for solving the problem]

[0006] This switch device has a composite including a first resin layer, a glass layer laminated on the underside of the first resin layer, and a second resin layer laminated on the underside of the glass layer, and a switch arranged on the underside of the second resin layer of the composite, wherein the thickness of the glass layer is 30 μm or more and 150 μm or less, and when the composite is pressed, the composite elastically deforms, causing the switch to switch between conductive and non-conductive states. Effect of the Invention

[0007] According to the disclosed technique, in a switch device including a composite having a glass layer, damage to the glass layer can be suppressed. [Brief description of the drawings]

[0008] [Figure 1] 1 is a cross-sectional view illustrating a switch device according to a first embodiment. [Diagram 2] 5A to 5C are diagrams illustrating the operation of the switch device according to the first embodiment. [Diagram 3] 1A to 1C are diagrams illustrating an experimental example and a reference example. [Figure 4] FIG. 1 is a diagram showing the measurement results of a feeling curve in Experimental Example 1. [Diagram 5] FIG. 13 is a diagram showing the measurement results of a feeling curve in Reference Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In the drawings, the same components are designated by the same reference numerals, and duplicated explanations may be omitted.

[0010] First embodiment Fig. 1 is a cross-sectional view illustrating a switch device according to a first embodiment. As shown in Fig. 1, the switch device 1 includes a composite 10, a bonding layer 20, a support portion 30, and a switch 40. The composite 10 also includes a first resin layer 11, a glass layer 12 laminated on the lower surface side of the first resin layer 11, and a second resin layer 13 laminated on the lower surface side of the glass layer 12.

[0011] The components of the switch device 1 will be described below.

[0012] [First resin layer] The first resin layer 11 has an upper surface 11a and a lower surface 11b that is the surface opposite to the upper surface 11a. The upper surface 11a side of the first resin layer 11 becomes the outermost surface of the switch device 1. The first resin layer 11 is flexible. From the viewpoint of flexibility, the thickness of the first resin layer 11 is preferably 50 μm or more and 100 μm or less.

[0013] Examples of materials for the first resin layer 11 include polyester-based resins such as polyethylene terephthalate-based resins and polyethylene naphthalate-based resins, cycloolefin-based resins such as norbornene-based resins, polyethersulfone-based resins, polycarbonate-based resins, acrylic-based resins, polyolefin-based resins, polyimide-based resins, polyamide-based resins, polyimideamide-based resins, polyarylate-based resins, polysulfone-based resins, polyetherimide-based resins, and urethane-based resins.

[0014] [Glass layer] The glass layer 12 has an upper surface and a lower surface that is the surface opposite to the upper surface. The upper surface is a single continuous surface. The lower surface is also a single continuous surface. The glass layer 12 preferably has high surface durability represented by a pencil hardness test of 9H or more and excellent dimensional stability.

[0015] The glass layer 12 is not particularly limited, and an appropriate glass layer can be adopted depending on the purpose. The glass layer 12 can be classified according to composition, for example, soda-lime glass, borate glass, aluminosilicate glass, quartz glass, etc. Also, according to alkali components, it can be non-alkali glass or low-alkali glass. The content of alkali metal components (e.g., Na2O, K2O, Li2O) in the above glass is preferably 15% by weight or less, more preferably 10% by weight or less.

[0016] Considering the surface hardness, airtightness, and corrosion resistance of glass, the thickness of the glass layer 12 is preferably 20 μm or more. Since the glass layer 12 needs to have flexibility and durability for repeated use like a film, the thickness of the glass layer 12 is preferably 150 μm or less. The thickness of the glass layer 12 is more preferably 30 μm to 120 μm, and particularly preferably 50 μm to 100 μm.

[0017] The glass layer 12 preferably has a light transmittance of 85% or more at a wavelength of 550 nm. The glass layer 12 preferably has a refractive index of 1.4 to 1.65 at a wavelength of 550 nm. The glass layer 12 preferably has a density of 2.3 g / cm 3 ~3.0g / cm 3 and more preferably 2.3 g / cm 3 ~2.7g / cm 3 It is.

[0018] The method for forming the glass layer 12 is not particularly limited, and an appropriate method can be adopted depending on the purpose. Typically, the glass layer 12 can be produced by melting a mixture containing a main raw material such as silica or alumina, an antifoaming agent such as mirabilite or antimony oxide, and a reducing agent such as carbon at a temperature of about 1400°C to 1600°C, forming it into a thin plate, and then cooling it. Examples of the method for forming the glass layer 12 include a slot downdraw method, a fusion method, and a float method. The glass layer formed into a plate by these methods may be chemically polished with a solvent such as hydrofluoric acid as necessary to make it thinner or to increase the smoothness.

[0019] The glass layer 12 may be made of tempered glass. The tempered glass may be chemically tempered glass or thermally tempered glass, but chemically tempered glass having a compressive stress layer is easier to manufacture than thermally tempered glass. When the glass layer 12 is made of tempered glass, it is preferable that the compressive stress is 600 MPa or more.

[0020] Chemical strengthening refers to replacing ions near the surface of a glass sheet with ions with a larger ionic radius. The ion exchange forms a compressive stress layer on the surface of the glass sheet, resulting in chemically strengthened glass. The glass composition in the compressive stress layer is different from the glass composition inside the glass.

[0021] In the chemically strengthened glass, the glass plate before strengthening can be, for example, soda-lime glass, aluminosilicate glass, borosilicate glass, aluminoborosilicate glass, etc. In that the depth of the compressive stress layer does not become too large more than necessary, soda-lime glass or soda-silicate glass is preferable, and soda-lime glass is more preferable.

[0022] Ion exchange can be carried out, for example, by substituting Li ions on the surface of the glass sheet with Na ions and / or K ions. Alternatively, Na ions on the surface of the glass sheet may be substituting K ions. By such ion exchange, a compressive stress layer is formed on the surface of the glass sheet.

[0023] When Na ions are replaced with K ions, for example, a glass plate containing sodium may be brought into contact with an inorganic molten salt containing potassium nitrate. The inorganic molten salt containing potassium nitrate preferably contains at least one salt selected from the group consisting of K2CO3, Na2CO3, KHCO3, NaHCO3, KOH, and NaOH.

[0024] [Second resin layer] The second resin layer 13 is laminated on the lower surface side of the glass layer 12. The second resin layer 13 has an upper surface and a lower surface that is the surface opposite to the upper surface. Details of the second resin layer 13 are the same as those of the first resin layer 11 already described. The first resin layer 11 and the second resin layer 13 may be formed of the same material or different materials. The first resin layer 11 and the second resin layer 13 may have the same thickness or different thicknesses. The thickness of the second resin layer 13 is preferably 50 μm or more and 100 μm or less from the viewpoint of flexibility.

[0025] A bonding layer may be provided between the lower surface of the first resin layer 11 and the upper surface of the glass layer 12. Also, a bonding layer may be provided between the upper surface of the second resin layer 13 and the lower surface of the glass layer 12. Any adhesive or bonding material described below may be used as the bonding layer. However, from the viewpoint of strength, it is preferable to use an adhesive as the bonding layer. From the viewpoint of appearance, the thickness of the bonding layer is preferably 0.5 μm or more and 25 μm or less, more preferably 0.5 μm or more and 5 μm or less, and even more preferably 0.5 μm or more and 3 μm or less.

[0026] [Joining layer] The bonding layer 20 bonds the second resin layer 13 and the support part 30 of the composite body 10. Any adhesive or adhesive can be used as the bonding layer 20. The thickness of the bonding layer 20 can be, for example, 5 μm or more and 20 mm or less.

[0027] In this specification, a pressure-sensitive adhesive refers to a layer that has adhesive properties at room temperature and adheres to an adherend with light pressure. Therefore, even when an adherend that has been stuck to the pressure-sensitive adhesive is peeled off, the pressure-sensitive adhesive retains practical adhesive strength. On the other hand, an adhesive refers to a layer that can bond substances by being interposed between them. Therefore, when an adherend that has been stuck to the adhesive is peeled off, the adhesive no longer has practical adhesive strength.

[0028] Examples of the adhesive include adhesives having an acrylic polymer, a silicone polymer, a polyester, a polyurethane, a polyamide, a polyether, a fluorine-based polymer, a rubber-based polymer, or the like as a base polymer.

[0029] Examples of adhesives include polyester adhesives, polyurethane adhesives, polyvinyl alcohol adhesives, and epoxy adhesives. When the adhesive is a thermosetting adhesive, it can be heated to harden (solidify) and exert its peel resistance. When the adhesive is a photocurable adhesive such as an ultraviolet-curable adhesive, it can be hardened by irradiating it with ultraviolet light or other light and exert its peel resistance. When the adhesive is a moisture-curable adhesive, it can be hardened by reacting with moisture in the air, and can be hardened by being left to stand and exert its peel resistance.

[0030] [Support part] The support part 30 is disposed on the lower surface side of the second resin layer 13 of the composite body 10. The support part 30 has, for example, a rectangular shape in a plan view. The support part 30 may have a shape other than a rectangular shape in a plan view. The support part 30 can be formed from, for example, a resin or a metal.

[0031] The support section 30 has an opening 30x and supports the composite 10 outside the opening 30x. The opening 30x is, for example, circular in plan view. In the example of FIG. 1, the opening 30x is a recess that opens on the upper surface side (the second resin layer 13 side) of the support section 30. In the example of FIG. 1, the opening 30x exposes the lower surface of the second resin layer 13. Note that the cross-sectional view of FIG. 1 shows a cross section cut along a plane that passes through the center of the opening 30x and is perpendicular to the upper surface of the support section 30.

[0032] The support portion 30 may have a plurality of openings 30x spaced apart from one another. The plurality of openings 30x may be arranged, for example, in a matrix in plan view. A switch 40 may be arranged in each of the openings 30x. Furthermore, one complex 10 may be arranged so as to cover the plurality of openings 30x.

[0033] [switch] The switch 40 is a switch that detects a physical change when pressed. At least a portion of the switch 40 is disposed inside the opening 30x of the support part 30. By operating the switch 40, a clicking sensation is obtained. In the example of FIG. 1, the switch 40 is a tactile switch that is disposed so that a movable part faces the lower surface of the second resin layer 13.

[0034] Switch 40 is not limited to a tactile switch, and may be any switch that provides a clicking sensation, such as a membrane switch. When switch 40 is a membrane switch, two sheets are arranged opposite each other to form a space that serves as an opening, and two terminals are arranged vertically opposite each other within the opening. In other words, when switch 40 is a membrane switch, a member that constitutes the switch serves as a support, and a part of the member that constitutes the switch (two terminals) is arranged within the opening of the support.

[0035] A member that is movable in the vertical direction independently of the composite body 10 may be sandwiched between the switch 40 and the lower surface of the second resin layer 13. This member is supported by the support portion 30 in a state in which it is movable in the vertical direction, for example, via a spring or the like. When the composite body 10 is pressed, the composite body 10 elastically deforms and presses this member, thereby switching the switch between conductive and non-conductive states.

[0036] 1, a gap is provided between the lower surface of the second resin layer 13 and the movable part of the switch 40, but the gap need not be provided. Also, a mechanism for transmitting deformation of the composite 10 to the switch 40 may be provided between the switch 40 and the second resin layer 13. It is preferable that the switch device 1 has a gap large enough that the switch 40 does not interfere with the flatness of the glass layer 12. However, it is preferable to have a gap large enough to operate the composite 10 when pressed down by 1 mm or less.

[0037] Fig. 2 is a diagram for explaining the operation of the switch device according to the first embodiment. As shown in Fig. 2, in the switch device 1, when the complex 10 is pressed in the direction of the arrow, the complex 10 elastically deforms and presses the movable part of the switch 40, switching between conductive and non-conductive states of the switch 40. When pressing the complex 10 is stopped, the complex 10 and the switch 40 return to the state shown in Fig. 1.

[0038] Thus, in the switch device 1, the composite 10 has a configuration including the glass layer 12 between the first resin layer 11 and the second resin layer 13. With such a configuration, even if the composite 10 repeatedly undergoes elastic deformation as shown in Fig. 2, damage to the glass layer 12 can be suppressed. Even if the glass layer 12 is damaged, the first resin layer 11 and the second resin layer 13 can suppress scattering, thereby realizing a switch device 1 that ensures safety.

[0039] The first resin layer 11 and / or the second resin layer 13 may have a structure in which a plurality of resin layers are laminated together. Such a laminated structure can further suppress breakage of the glass layer 12 and improve the durability of the glass layer 12 when it is repeatedly elastically deformed.

[0040] In the composite body 10 of the switch device 1, it is preferable that the thickness of the glass layer 12 is 30 μm or more and 150 μm or less, and the total thickness of the first resin layer 11 and the second resin layer 13 is 1 time or more and 5 times or less the thickness of the glass layer 12. Within these ranges, it is possible to realize a switch device 1 that can suppress breakage of the glass layer 12 and provide a substantially constant clicking sensation.

[0041] <Experimental Examples, Reference Examples> The inventors have studied a switch device capable of suppressing breakage of a glass layer, and have also evaluated a feeling curve.

[0042] [Experimental Example 1] (glass layer) A glass film (OA-10, manufactured by Nippon Electric Glass Co., Ltd.) having a thickness of 100 μm was cut into a 10 cm square to form a glass layer.

[0043] (Preparing the adhesive) An adhesive solution was prepared by mixing an epoxy resin (Celloxide 2021P, Daicel Chemical Industries, Ltd.), an oxetane resin (Aron Oxetane OXT-221, Toa Gosei Co., Ltd.), a polymerization initiator (Adeka Optomer SP-170, ADEKA Corporation), and a coupling agent (KBM-403, Shin-Etsu Chemical Co., Ltd.) in a ratio of 90:10:3:2.

[0044] (Preparation of resin film) As the resin films to become the first resin layer and the second resin layer, one PET film (Cosmoshine 100 A4360, manufactured by Toyobo Co., Ltd.) having a thickness of 100 μm was prepared.

[0045] (Preparation of Complex) An adhesive was applied to the surfaces of the two resin films to a thickness of 5 μm to form a coating layer. The two resin films were then attached to both sides of the glass layer via the coating layer. After that, ultraviolet light was irradiated from a high-pressure mercury lamp (wavelength: 365 nm, intensity: 1000 mJ / cm 2 The coating layer was cured by the above steps to obtain a composite body in which the first resin layer, the glass layer, and the second resin layer were laminated.

[0046] (Formation of bonding layer) An adhesive sheet (CS9862UA, manufactured by Nitto Denko) with a hole of φ25 mm was attached to the lower surface of the second resin layer of the composite to form a bonding layer.

[0047] (Creating a switch device) A rectangular support with an opening as shown in Figure 1 was prepared. The height of the support was 300 mm, and the opening was a cylindrical recess with a diameter of 25 mm. Next, a switch (SKQM-ARE010, manufactured by Alps Alpine Co., Ltd.) was placed in the opening, and the bonding layer formed on the composite was attached to the upper surface of the support to produce a switch device with a structure similar to that of Figure 1. At that time, the part on which the bonding layer was not formed was placed so as to overlap the opening of the support. In addition, the distance between the lower surface of the second resin layer and the switch was set to 0.2 mm.

[0048] (Rating 1: Damaged) The fabricated switch device was subjected to damage measurement. To measure damage, a spring impact hammer (PTL-Instruments GmbH, impact 0.5J) was used to perform a test perpendicular to the switch through the composite body in accordance with the JISC60068 standard. After the test, the glass layer was checked for damage and shattering.

[0049] (Rating 2: Feeling Curve) The feeling curve was measured for the switch device that was produced. To measure the feeling curve, an Aiko Engineering switch feeling tester GT-FL500 was used, and the push-in load was set to return to the origin at 20N. The feeling curve was measured multiple times, and it was confirmed whether the shape of the curve changed when the number of measurements was increased. Small changes were marked with ◯, and large changes were marked with ×.

[0050] [Experimental Example 2] A switching device was produced in the same manner as in Experimental Example 1, except that the thickness of the glass layer was 30 μm and the thickness of the PET film serving as the second resin layer was 50 μm, and evaluations were performed in the same manner as in Experimental Example 1.

[0051] [Experimental Example 3] A switching device was produced in the same manner as in Experimental Example 1, except that the thickness of the PET film serving as the first resin layer was 50 μm and the thickness of the glass layer was 150 μm, and an evaluation similar to that of Experimental Example 1 was performed.

[0052] [Experimental Example 4] A switch device was fabricated in the same manner as in Experimental Example 1, except that the thickness of the PET film constituting the first resin layer was 188 μm, the thickness of the glass layer was 30 μm, and the thickness of the PET film constituting the second resin layer was 188 μm, and an evaluation was performed in the same manner as in Experimental Example 1.

[0053] [Experimental Example 5] A switching device was produced in the same manner as in Experimental Example 1 except that the thickness of the glass layer was set to 200 μm, and an evaluation similar to that in Experimental Example 1 was carried out.

[0054] [Reference example 1] A switching device was produced in the same manner as in Experimental Example 1, except that the composite was formed only from a second resin layer made of a 100 μm-thick PET film (Cosmoshine 100 A4360, manufactured by Toyobo Co., Ltd.), and evaluation was performed in the same manner as in Experimental Example 1.

[0055] [Reference example 2] A switching device was produced in the same manner as in Experimental Example 1 except that the first resin layer was not provided, and an evaluation was performed in the same manner as in Experimental Example 1.

[0056] [Evaluation Results] The experimental examples and the reference examples are summarized in Figure 3. The thickness ratio of the glass layer to the resin layer is also shown in Figure 3. The thickness of the resin layer here is the sum of the thickness of the first resin layer and the thickness of the second resin layer.

[0057] The measurement results of the feeling curve of Experimental Example 1 are shown in Fig. 4, and the measurement results of the feeling curve of Reference Example 1 are shown in Fig. 5. In Fig. 4 and Fig. 5, the feeling curve was measured three times, with N=1 indicating the result of the first measurement, N=2 indicating the result of the second measurement, and N=3 indicating the result of the third measurement.

[0058] (Whether or not the glass layer is damaged) As shown in Fig. 3, in a configuration in which the outermost surface is a glass layer as in Reference Example 2, the glass layer was broken and scattered. On the other hand, in the configurations in which a glass layer is provided between the first resin layer and the second resin layer as in Experimental Examples 1 to 5, no breakage of the glass layer was observed. That is, it was confirmed that breakage of the glass layer can be suppressed by providing a glass layer between the first resin layer and the second resin layer.

[0059] (Curve shape) Concerning the curve shape, good results were obtained in Experimental Examples 1 to 3 and Reference Example 2. Comparing Experimental Examples 1 to 3 with Experimental Examples 4 and 5, it can be seen that the shape of the curve changes depending on the thickness of the glass layer and the ratio of the thickness of the glass layer to the resin layer. Also, Fig. 4 confirms that in Experimental Example 1, the change in the curve over three measurements is small, while Fig. 5 confirms that in Reference Example 1, the change in the curve over three measurements is large.

[0060] In addition, from the results of FIG. 3, it can be seen that, with regard to the shape of the curve, in a composite having a glass layer between the first resin layer and the second resin layer, the thickness of the glass layer is preferably 30 μm or more and 150 μm or less, and the ratio of the thickness of the glass layer to the thickness of the resin layer is preferably 1:1 or more and 1:5 or less. In other words, it can be seen that it is preferable that the thickness of the glass layer is 30 μm or more and 150 μm or less, and that the total thickness of the first resin layer and the second resin layer is 1 time or more and 5 times or less the thickness of the glass layer. In such a range, the operation feeling when the switch is pressed does not vary, so that a substantially constant clicking sensation can be obtained. In other words, in addition to the effect of suppressing breakage of the glass layer, a substantially constant clicking sensation can be obtained. By providing a substantially constant clicking sensation, the switch can be operated accurately without any discomfort.

[0061] Although preferred embodiments have been described above in detail, the present invention is not limited to the above-described embodiments, and various modifications and substitutions can be made to the above-described embodiments without departing from the scope of the claims.

[0062] In addition to the above-described embodiment, the following supplementary notes are further disclosed. (Appendix 1) a composite including a first resin layer, a glass layer laminated on a lower surface side of the first resin layer, and a second resin layer laminated on a lower surface side of the glass layer; a switch disposed on a lower surface side of the second resin layer of the composite body, The thickness of the glass layer is 30 μm or more and 150 μm or less, When the complex is pressed, the complex is elastically deformed, causing the switch to switch between conductive and non-conductive states. (Appendix 2) 2. The switch device according to claim 1, wherein a total thickness of the first resin layer and the second resin layer is greater than or equal to 1 time and less than or equal to 5 times a thickness of the glass layer. (Appendix 3) 3. The switch device according to claim 1, wherein the first resin layer has a thickness of 50 μm or more and 100 μm or less. (Appendix 4) 4. The switch device according to claim 1, wherein the second resin layer has a thickness of 50 μm or more and 100 μm or less. (Appendix 5) a support portion that is disposed on a lower surface side of the second resin layer of the composite, has an opening, and supports the composite outside the opening; 5. The switch device according to claim 1, wherein the switch is disposed inside the opening. (Appendix 6) the opening exposes a lower surface of the second resin layer, 6. The switch device according to claim 5, wherein the switch is a tactile switch arranged so that a movable part faces a lower surface of the second resin layer. [Explanation of symbols]

[0063] 1 Switching device 10 Complex 11 First resin layer 11a Top side 11b Bottom side 12 Glass layer 13 Second resin layer 20 Bonding layer 30 Support part 30x opening 40 Switch

Claims

1. a composite including a first resin layer, a glass layer laminated on a lower surface side of the first resin layer, and a second resin layer laminated on a lower surface side of the glass layer; a switch disposed on a lower surface side of the second resin layer of the composite body, The thickness of the glass layer is 30 μm or more and 150 μm or less, When the complex is pressed, the complex is elastically deformed, causing the switch to switch between conductive and non-conductive states.

2. The switch device according to claim 1 , wherein a total thickness of the first resin layer and the second resin layer is equal to or greater than 1 time and equal to or less than 5 times a thickness of the glass layer.

3. The switch device according to claim 1 or 2, wherein the first resin layer has a thickness of 50 μm or more and 100 μm or less.

4. The switch device according to claim 1 or 2, wherein the second resin layer has a thickness of 50 μm or more and 100 μm or less.

5. a support portion that is disposed on a lower surface side of the second resin layer of the composite, has an opening, and supports the composite outside the opening; The switch device according to claim 1 or 2, wherein the switch is disposed inside the opening.

6. the opening exposes a lower surface of the second resin layer, The switch device according to claim 5 , wherein the switch is a tactile switch arranged such that a movable portion faces the lower surface of the second resin layer.

Citation Information

Patent Citations

  • Switch device

    JP2022166480A